Ganglioside GM1/galectin-dependent growth regulation in human neuroblastoma cells: special properties of bivalent galectin-4 and significance of linker length for ligand selection - Kopitz, Jürgen; Ballikaya, Seda (Neurochemical research, 2012)
Orchestrated upregulation of cell surface presentation of ganglioside GM1 and homodimeric galectin-1 is the molecular basis for growth regulation of human neuroblastoma (SK-N-MC) cells. Further study led to the discovery of competitive inhibition by galectin-3, prompting us to test tandem-repeat-type galectin-4 (two different lectin domains connected by a 42-amino-acid linker). This lectin bound to cells at comparably high affinity without involvement of the ganglioside, as disclosed by assays in the presence of cholera toxin B-subunit or galectin-1 and blocking glucosylceramide synthesis. Notably, when tested separately, binding of both lectin domains showed partial sensitivity to the bacterial agglutinin. Despite its ability for cross-linking surface association of galectin-4 did not affect proliferation, in contrast to homodimeric galectins. The truncation of linker length from 42 to 16 amino acids altered binding properties to let partial sensitivity to the bacterial lectin emerge. Cross-competition between parental and engineered proteins did not exceed 40%. No effect on cell growth was detected. This study reveals complete functional divergence between galectins differing in the spatial mode of lectin-site presentation and dependence of reactivity to distinct counter-receptor(s) on linker length. Due to the documented presence of galectin-4 in the nervous system and its affinity for sulfatide these in vitro results indicate the potential for a distinct functionality profile of this lectin in vivo, giving further research direction.